2016
DOI: 10.1186/s13023-016-0534-8
|View full text |Cite
|
Sign up to set email alerts
|

Current models of care for disorders of sex development – results from an International survey of specialist centres

Abstract: BackgroundTo explore the current models of practice in centres delivering specialist care for children with disorders of sex development (DSD), an international survey of 124 clinicians, identified through DSDnet and the I-DSD Registry, was performed in the last quarter of 2014.ResultsA total of 78 (63 %) clinicians, in 75 centres, from 38 countries responded to the survey. A formal national network for managing DSD was reported to exist in 12 (32 %) countries. The paediatric specialists routinely involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 27 publications
(26 reference statements)
3
77
0
Order By: Relevance
“…Unfortunately, more than a decade after the 2006 Consensus statement which highlighted the importance of multidisciplinary care [1], many DSD teams still do not offer universal comprehensive services, and often lack, in particular, behavioral health providers [18, 19]. Barriers to inclusion of behavioral health in DSD comprehensive care have not been delineated but likely include lack of access to behavioral health providers (with DSD expertise, especially), inadequate funding models for multidisciplinary care [20], and/or the financial and stigma-related barriers found in rural or remote resource-poor communities [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, more than a decade after the 2006 Consensus statement which highlighted the importance of multidisciplinary care [1], many DSD teams still do not offer universal comprehensive services, and often lack, in particular, behavioral health providers [18, 19]. Barriers to inclusion of behavioral health in DSD comprehensive care have not been delineated but likely include lack of access to behavioral health providers (with DSD expertise, especially), inadequate funding models for multidisciplinary care [20], and/or the financial and stigma-related barriers found in rural or remote resource-poor communities [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…However, even though it seems that most primary care centres include this subspecialty as part of the MDT [Pasterski et al, 2010b;Kyriakou et al, 2016], one study of practices across Europe found that the majority of families were not taking up the offer of psychological support [Pasterski et al, 2010b]. One interpretation of this finding is that patients and families may associate psychological support with mental illness and may have found the prospect stigmatizing.…”
Section: Objectives Of Psychological Evaluationmentioning
confidence: 89%
“…While there is agreement that DSD care requires an experienced interprofessional team (Hughes et al, 2006, p.555), what constitutes an experienced team and how this is differentiated from other types of working is unclear. While the professional composition of the team is described elsewhere (Gomez-Lobo, 2014; Streuli, Köhler, Werner-Rosen, & Mitchell, 2012), variation exists globally (Kyriakou et al, 2016). An online study examined the status of the consensus statement implementation across Europe (Pasterski, Prentice, & Hughes, 2010).…”
Section: Introductionmentioning
confidence: 99%